2019
DOI: 10.1021/acsanm.9b01924
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Hydrogel Composed of Carboxymethylcellulose–Silver Nanoparticles–Doxorubicin for Anticancer and Antibacterial Therapies against Melanoma Skin Cancer Cells

Abstract: Malignant melanoma is the utmost severe form of skin cancer, causing the vast majority of deaths related to skin cancer in humans. Although melanoma is treatable at its early stages at localized forms, metastatic melanoma remains a therapeutic challenge with dramatically increased incidence in the past few years. In addition, opportunistic pathogens can provoke infections leading to ulceration of cutaneous melanoma. Herein, we designed and synthesized hybrid hydrogels made of silver nanoparticles (AgNPs) embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 60 publications
0
57
0
Order By: Relevance
“…Compared with silver ions, the antibacterial activity of CMC-SNs prepared by the method reported in this paper is slightly lower, which is consistent with similar results reported in the literature. However, it has been reported that the silver nanoparticles coated with polysaccharide have the characteristic of slow release [ 25 ], which may be more suitable for the control of rice bacterial diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with silver ions, the antibacterial activity of CMC-SNs prepared by the method reported in this paper is slightly lower, which is consistent with similar results reported in the literature. However, it has been reported that the silver nanoparticles coated with polysaccharide have the characteristic of slow release [ 25 ], which may be more suitable for the control of rice bacterial diseases.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, hybrid system also showed good antimicrobial potentials against different Gram-positive and Gram-negative bacteria. Thus, an innovative hybrid hydrogels platform was produced with anticancer and antibacterial properties and could be successfully applied as a weapon against skin cancer (Capanema et al, 2019 ).…”
Section: Applications Of Hybrid Hydrogelsmentioning
confidence: 99%
“…Capanema and collaborators designed and synthesized hybrid hydrogels made of silver nanoparticles (AgNPs) embedded a carboxymethylcellulose (CMC)-based hydrogel conjugated with doxorubicin (DOX), an anticancer drug [ 60 ]. This system was synthesized by a green process, using an in situ reduction of Ag+ by CMC polymer, which also acted as capping ligand, followed by the electrostatic conjugation with DOX, with the formation of colloidal nanocomplexes in aqueous media.…”
Section: Nanoparticles Useful For Melanoma Treatmentmentioning
confidence: 99%